Dynamic evolution of V1R putative pheromone receptors between Mus musculus and Mus spretus - Kurzweil, Vanessa C; Getman, Mike; Green, Eric D; Lane, Robert P (BMC genomics, 2009)
Background The mammalian vomeronasal organ (VNO) expresses two G-protein coupled receptor gene families that mediate pheromone responses, the V1R and V2R receptor genes. In rodents, there are ~150 V1R genes comprising 12 subfamilies organized in gene clusters at multiple chromosomal locations. Previously, we showed that several of these subfamilies had been extensively modulated by gene duplications, deletions, and gene conversions around the time of the evolutionary split of the mouse and rat lineages, consistent with the hypothesis that V1R repertoires might be involved in reinforcing speciation events. Here, we generated genome sequence for one large cluster containing two V1R subfamilies in Mus spretus, a closely related and sympatric species to Mus musculus, and investigated evolutionary change in these repertoires along the two mouse lineages. Results We describe a comparison of spretus and musculus with respect to genome organization and synteny, as well as V1R gene content and phylogeny, with reference to previous observations made between mouse and rat. Unlike the mouse-rat comparisons, synteny seems to be largely conserved between the two mouse species. Disruption of local synteny is generally associated with differences in repeat content, although these differences appear to arise more from deletion than new integrations. Even though unambiguous V1R orthology is evident, we observe dynamic modulation of the functional repertoires, with two of seven V1Rb and one of eleven V1Ra genes lost in spretus, two V1Ra genes becoming pseudogenes in musculus, two additional orthologous pairs apparently subject to strong adaptive selection, and another divergent orthologous pair that apparently was subjected to gene conversion. Conclusion Therefore, eight of the 18 (~44%) presumptive V1Ra/V1Rb genes in the musculus-spretus ancestor appear to have undergone functional modulation since these two species diverged. As compared to the rat-mouse split, where modulation is evident by independent expansions of these two V1R subfamilies, divergence between musculus and spretus has arisen more by mutations within coding sequences. These results support the hypothesis that adaptive changes in functional V1R repertoires contribute to the delineation of very closely related species.